Evolution of dayside chorus into nightside plasmaspheric hiss - Bortnik, Jacob; Chen, Lunjin; Zhang, Xiao-Jia; Meredith, Nigel P. (Frontiers in Astronomy and Space Sciences, 2025)
Plasmaspheric hiss is an incoherent, broadband, whistler-mode emission that is found primarily in the Earth’s dense plasmasphere and is believed to be largely responsible for the formation of the slot region between the inner and outer radiation belts. Beginning with the earliest observations of plasmaspheric hiss in the 1970s, it was noticed that duskside hiss emissions tended to disappear during the main phase of geomagnetic storms, and reappear again during the recovery phase. Here, we perform extensive ray tracing in a realistic, three-dimensional cold plasma density model that evolves during the course of a storm. On the basis of these simulations, we show that the formation of a broad, dayside plasmaspheric plume during the main phase of the storm prevents access of dayside chorus rays to the plasmaspheric dusk-midnight region, which explains the observed disappearance of plasmaspheric hiss waves in this region. In the recovery phase of the storm, however, the narrow, rotated plume and eroded plasmasphere create the ideal conditions for dayside chorus rays to propagate into the plasmasphere, attain a large azimuthal propagation component, and ‘hop’ over the narrow plume, thus enabling them to access the dusk-midnight region and explaining the observed reappearance of duskside hiss waves in the storm recovery phase.